La política de acceso y uso de Internet en las bibliotecas públicas: análisis comparativo y modelo - Pacios Lozano, Ana Reyes; Ameneiros Rodríguez, Rocío (Revista General de Información y Documentación, 2005)
Public libraries with website and offering Internet-access service are, particularly in English-speaking countries, increasingly including their use conditions. To determine the essential contents of the rules or policies that regulate such services, we are carrying out a comparative analysis of some documents found in the websites of public libraries of English-speaking and French-speaking countries, as well as of our own country.